Endovascular Repair of a Dacron Pseudoaneurysm in an Ascending-to-Descending Aortic Bypass - Tomasi, Jacques; Belhaj Soulami, Reda; Rolland, Marion; Verhoye, Jean-Philippe (AORTA, 2020)
In the setting of postcoarctation aortic repair, Dacron graft dilatation and late aneurysms are not uncommon. Reintervention usually involves redo open surgery and replacement of the aneurysmal graft or the pseudoaneurysmal suture line. The present case describes the endovascular repair of a Dacron anastomotic false aneurysm in an extra-anatomic ascending-to-descending aortic bypass, 19 years after surgical correction of aortic recoarctation.
Keywords: aortic coarctation; aneurysm; endovascular repair; pseudoaneurysm